An integrated approach to re-evaluate the validity of the family Leptobathynellidae (Crustacea: Bathynellacea). Issue 3 (18th February 2021) - Camacho, Ana I; Mas-Peinado, Paloma; Reddy, Yenumula Ranga; Bandari, Elia; Shaik, Shabbudin; Perina, Giulia; Dorda, Beatriz A; Casado, Adrian; Rey, Isabel
Abstract: The systematic status of the controversial crustacean family Leptobathynellidae is investigated using molecular and morphological methods in this study. Partial sequences of the nuclear 18S gene are studied from 28 genera of Bathynellacea from several continents. The analysis includes some of the most plesiomorphic genera of the family Parabathynellidae, such as Billibathynella and Brevisomabathynella from Australia; Habrobathynella and Parvulobathynella from India; the diverse Iberobathynella ; the cosmopolitan genus Hexabathynella ; and representative genera of two subfamilies of Bathynellidae (Gallobathynellinae and Bathynellinae). We used a molecular approach to analyse the systematic relationships amongst 64 species from Europe, North America, Australia and Asia, and review the morphological characters relevant at the family level. The molecular phylogeny clearly shows the presence of three highly divergent clades that could represent the three families. This is the first molecular phylogenetic reconstruction of Bathynellacea that can be used to: (1) verify the validity of Leptobathynellidae, (2) explore the diversity of the families and (3) explore the phylogenetic relationships among families. We propose a plausible evolutionary scenario for the order Bathynellacea.